Effects of Temperature on Hydrocarbon Fractions Obtained by Catalytic Pyrolysis of Low Density Polyethylene - Sangeeta Hanumant Deshpande, N. V. Iyer, M. Y. Khaladkar, M. R. Shindikar, G. L. Agawane, Yogeshwari B. Sonawane, J. A. Kher (International Journal of Advanced Science and Technology, 2019)
In this study, attempts have been made to understand chemical composition of fractions obtained during pyrolysis of Low Density Polyethylene (LDPE) collected after condensation. The experiments are conducted with and without different catalysts in temperature range between 500C and 3000C. The characterization of the collected fractions is carried out by Fourier Transform Infrared Spectroscopy [FTIR] to know composition and structure. Using FTIR technique it is concluded that the fractions obtained contain presence of ketone, ether and alkyl fractions. The most significant observation is during the second stage of distillation that fractions are collected at temperatures well below the reported temperatures in the range of 500 to 4500C and above . Keyword:. LDPE, Pyrolysis, FTIR